Penanaman Nilai Kearifan Lokal Melalui Konsep Profil Pelajar Pancasila di Sekolah Dasar - Nur Arfiyah Ghina Rokhimah; Lu’luil Maknun (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2022)
The Pancasila Student Profile is a character strengthening in education, especially among the younger generation. The character which is the ideology of the nation can be formed from the diversity of local wisdom. The introduction of the values ​​of local wisdom to students is very important because the values ​​of local wisdom are one part of the manifestation of the nation's cultural wealth. This study aims to describe the cultivation of local wisdom values ​​through the concept of the Pancasila student profile so that it can be implemented in everyday life. The method used is a library approach (data collection method in the form of documents in the form of books, literature, and scientific journals). Based on the results of the study through the application of the 6 dimensions of the Pancasila student profile, it is expected that students will become intelligent and characterized individuals by applying local wisdom values ​​and being able to face the challenges of the 21st century and course instilling the values ​​contained in Pancasila.